Are Monetary and Fiscal Policies Effective in Controlling Budget Deficits? - Rachmawaty Rachmawaty; Jaja Suteja; Atang Hermawan (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2024)
The state budget's countercyclical policy and government revenue imbalance to support government expenses caused Indonesia to experience a budget deficit for years. Understanding the correlation between monetary and fiscal policies helps policy makers formulate effective strategies to control and manage budget deficits. The research’s novelty is the complexity variable, which consists of three variable classifications. The first is monetary policy ( interest rates and money supply), the second is fiscal policy (government revenue and expenses), and the third is macroeconomic variables: economic growth, inflation, and exchange rate. All data is processed using the VAR/VECM in EVIEWS 9. The finding is that fiscal policy consists of controlling revenue and expenses, giving 37.6% contribution; monetary policy consists of the number of broad money and BI Rate give 7.6% contribution; macroeconomic factor consists of exchange rate, inflation and economic growth, giving contribution 41.6% while the effect of budget deficit itself has contribution 13.2%. The result of Granger Causality show that government revenue, economic growth and BI rate has a causality impact to budget deficit. Controlling those three variables will directly impact the budget deficit.